The Impact of Ethical and Legal Decision-Making in Neonatal Intensive Care on Psychosocial Wellbeing of the Health Care Professionals: The Overview of the HUNIC Project Study Design - Feith, Helga Judit; Soósné Kiss, Zsuzsanna; Pilling, János; Kovács, Aranka; Szabó, Miklós; Cuttini, Marina; Berbik, István; Gézsi, András; Gradvohl, Edina (European Journal of Mental Health, 2019)
The paper introduces the multidisciplinary HUNIC project, which is partly based on the EURONIC study. The objective of the HUNIC study is to assess the attitude and opinion of healthcare providers in Hungarian NICUs about end-of-life decisions, the decision-making process, parental communication, to analyse the differences between HUNIC results in 2015-2016 and EURONIC results in 1996-1997, to compare the attitudes of neonatologists and neonatal nurses, and to identify factors that might affect those attitudes and opinions. A further important objective of the HUNIC study is to compare these attitudes and opinions of neonatal care providers with their personal work experience, educational background in the bioethics field, social support, work and life satisfaction, burnout, health behaviour and psychosocial health. This paper aims to present the methodology of an extensive, complex, and multidisciplinary survey (HUNIC) within the framework of the EURONIC.